ANALISIS NON PERFORMING LOAN TERHADAP CAPITAL ADEQUACY RATIO PADA PT BCA Tbk - Simanjuntak, Evelyn Angelia; Aurelya Zai, Cindy Tania; Nauli Sinaga, Elisabet Sihol; Silitonga, Cristin Erni Juliani; Sitompul, Ibrani Natasya; Hasugian, Christnova; Siallagan, Hamonangan (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the relationship between Non-Performing Loan (NPL) and Capital Adequacy Ratio (CAR) at PT Bank Central Asia Tbk (BCA). NPL is an indicator of non-performing loans that reflect credit risk in banking, while CAR reflects the adequacy of capital in bearing financial risks. The results showed that there is a negative relationship between NPL and CAR with a correlation coefficient of -0.520, although it is not statistically significant with a significance value of 0.652 (>0.05). In addition, the coefficient of determination analysis shows that NPL contributes 27.04% to changes in CAR, while the rest is influenced by other factors not examined in this study. This study provides insights for bank management and regulators in improving credit risk management strategies to maintain national banking stability.